On a Class of Nonuniformly Nonlinear Systems with Dirichlet Boundary Conditions - Afrouzi, G. A.; Naghizadeh, Z.; Chung, N. T. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
The existence and multiplicity of weak solutions for some nonuniformly nonlinear elliptic systems are obtained by using the minimum principle and the Mountain-pass theorem.